EFFECT OF FINANCIAL PERFORMANCE, DIVIDEND POLICY AND CAPITAL STRUCTURE ON THE VALUE OF THE COMPANY: PENGARUH KINERJA KEUANGAN, KEBIJAKAN DIVIDEN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Norma Islami; Rudi Zulfikar; Iis Ismawati (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
Objectives To empirically test the effect of financial performance, dividend policy, capital structure on firm value in banking sub-sector companies on the Indonesia Stock Exchange (IDX). This type of research includes quantitative research. The method used is secondary data, then processed and finally analyzed using the Multiple Linear Regression Analysis equation. The data is then tested descriptively, after testing the data then tested using the classical multiple regression assumption test. The classical assumption test used consisted of normality test, multicollinearity test and heteroscedasticity test, autocorrelation. Then the data were analyzed using the coefficient of determination test, partial test (t) and simultaneous test (f). The results of this study are the Effect of Financial Performance (X1), Dividend Policy (X2), Capital Structure (X3) on Firm Value (Y) in banking sub-sector companies on the Indonesia Stock Exchange (IDX). Financial Performance (X1) has a positive and significant effect on Firm Value (Y). Dividend Policy (X2) has a positive and significant effect on Firm Value (Y). Capital Structure (X3) has a positive and significant effect on Firm Value (Y).